Analisis Yuridis Penyimpanan Minuta Akta Notaris Secara Elektronik - Engelbert, Lendo Theo; Widhianti, Hanif Nur; Wisnuwardhani, Diah Aju (Universitas Negeri Malang, 2021)
This study aimed to discuss and analyze problems regarding the storage of minutes of notary deeds made electronically. This study used a normative research method. The approach used a statutory approach and a conceptual approach. The minutes of the notarial deeds can be made electronically because they were permitted by several regulations. Electronic deed minutes can be stored as long as the original deed was still made and stored conventionally. The validity of the position of the minutes of the determined that was stored electronically as evidence was determined by the judge's consideration.